Clinical, dermoscopic, and mycological association in onychomycosis in a tertiary care hospital - Daksha Vasava; Hita Mehta; Twinkle Patel; Milan Jhavar; Rahul Lakhotia (Wolters Kluwer Medknow Publications, 2021)
Background: Onychomycosis (OM) refers to fungal infection of the nail unit. It is one of the most common nail disorders, accounting for 50% of all nail disorders and about 30% of all cutaneous fungal infections. OM is mostly diagnosed clinically, but Dermoscopic (DS) examination aids in diagnosis. Objectives: The purpose of the study is to study the association between clinical, dermoscopic, and mycological patterns of OM. Materials and Methods: A total of 200 patients with clinical suspicion of OM were included in the study. All patients underwent clinical examination, dermoscopic examination with a handheld dermoscope Dermlite II pro (3 Gen, San Juan, Capistrano, CA, USA) with a ×10 magnification, KOH assessment, and culture analysis. The most frequent dermoscopic patterns were identified and their associations with the clinical subtype of OM were analyzed. Results: Out of the 200 cases, 65 cases were male and 135 cases were female. The most common findings seen on clinical examination of nails were discoloration of nail plates (178) and onycholysis (109). Distal irregular termination (91) was the most common dermoscopic finding seen followed by spike pattern (76). A significant association was seen between dermoscopic patterns such as superficial transverse striation, spike pattern, and different types of OM (P < 0.05). Eighty-two cases were positive for fungal elements by direct microscopy, 68 were positive by culture, and 18 patients showed positive result for both. The most common causative organism found on culture examination was Candida albicans (24). Conclusion: Dermoscopy is an easy-to-perform, noninvasive, and cost-effective method which aids in early diagnosis of OM.